Does External Rotation Bracing for Anterior Shoulder Dislocation Actually Result in Reduction of the Labrum?: A Systematic Review. (September 2015) - Jordan, Robert W.; Saithna, Adnan; Old, Jason; MacDonald, Peter
Background: External rotation (ER) bracing has been shown to improve labral reduction in cadaveric studies, but this has not translated to universal improvement in re-dislocation rates in clinical series. Purpose: To systematically review and critically appraise the literature that investigates how well the labrum is actually reduced by ER in patients who have had an anterior shoulder dislocation. Study Design: Systematic review. Methods: We conducted a systematic review of the literature using the online databases Medline, EMBASE, and the Cochrane Controlled Trial Register. Studies were included if they reported on the difference in labral reduction after ER and internal rotation bracing in patients who had a traumatic anterior shoulder dislocation. Results: Of the 6 studies included, 5 assessed labral reduction on magnetic resonance imaging and 1 arthroscopically. Each study reported an overall improvement in labral reduction with ER, but anatomic reduction was not commonly achieved. This was despite the use of extreme positions that are unlikely to be well tolerated. Conclusion: External rotation results in anatomic reduction of the labrum in only 35% of cases. We postulate that failure to reduce the labrum may be a contraindication to ER bracing and propose further study to determine whether acute MRI could be used to help identify patients in whom ER achieves labral reduction in a comfortable position. This approach also has the advantage of avoiding the significant inconvenience of ER bracing in those in whom the labrum does not reduce and are therefore theoretically less likely to benefit. However, it is a novel strategy with significant resource implications and therefore warrants further study.